Ex vivo dissection increases lymph node yield in oesophagogastric cancer. Issue 1 (26th August 2013) - Cichowitz, Adam; Burton, Paul; Brown, Wendy; Smith, Andrew; Shaw, Kalai; Slamowicz, Ron; Nottle, Peter D.
Abstract Background Retrieval and analysis of an adequate number of lymph nodes is critical for accurate staging of oesophageal and gastric cancer. Higher total node counts reported by pathologists are associated with improved survival. A prospective study was undertaken to understand the factors contributing to variability in lymph node counts after oesophagogastric cancer resections and to determine whether a novel strategy of ex vivo dissection of resected specimens into nodal stations improves node counts reported by pathologists. Methods The study involved 88 patients with potentially curable oesophagogastric cancer undergoing radical resection. Lymph node counts were obtained from pathology reports and analysed in relation to multiple variables including the introduction of ex vivo dissection of nodal stations in theatre. Results Higher lymph node counts were obtained with ex vivo dissection of nodal stations (median 19 versus 8, P < 0.01). Node counts also varied significantly with the reporting pathologist (median range 4 to 48, P = 0.02) which was independent of the level of experience of the pathologist (P = 0.67). Node counts were not affected by patient age (P = 0.26), gender (P = 0.50), operative approach (P = 0.50) or neoadjuvant therapy (P = 0.83). Conclusions Specimen handling is a significant factor in determining lymph node yield following radical oesophageal and gastric cancer resections. Ex vivo dissection of resected specimens into nodal stations improves node counts without alterations to surgical techniques. Ex vivo dissection should be considered routine.